Spectral imaging of the central molecular zone in multiple 7-mm molecular lines - Jones, P.; Burton, M.; Cunningham, M.; Tothill, N.; Walsh, Andrew (Oxford University Press, 2013)
We have imaged 24 spectral lines in the central molecular zone (CMZ) around the Galactic Centre, in the range 42–50 GHz. The lines include emission from the CS, CH3OH, HC3N, SiO, HNCO, HOCO+, NH2CHO, OCS, HCS+, CCS, C34S, 13CS, 29SiO, H13CCCN, HCC13CN and HC5N molecules, and three hydrogen recombination lines. The area covered is Galactic longitude −0.7 to 1.8and latitude −0.3 to 0.2, including the bright cores around Sgr A, Sgr B2, Sgr C and G1.6-0.025. This work used the 22-m Mopra radio telescope in Australia, obtaining ~1.8 km s−1 spectral and ~ 65 arcsec spatial resolutions. We present peak images from this study and conduct a principal component analysis on the integrated emission from the brightest 10 lines, to study similarities and differences in the line distribution. We examine the integrated line intensities and line ratios in selected apertures around the bright cores, as well as for the complete mapped region of the CMZ. We compare these 7-mm lines to the corresponding lines in the 3-mm band, for five molecules, to study the excitation. There is a variation in 3 to 7-mm line ratio across the CMZ, with relatively higher ratio in the centre around Sgr B2 and Sgr A. We find that the lines are sub-thermally excited, and from modelling with RADEX find that non-Local Thermodynamic Equilibrium conditions apply, with densities of the order of 104 cm−3.